Digital Government 2020 : Prospects for Russia - World Bank Group (World Bank, Washington, DC, 2016)
Governments around the world are facing a double challenge. Their citizens are expecting everhigher standards of service and want to be able to interact with the government online as easily as they do with banks and Internet commerce companies. At the same time, governments need to reduce administrative costs and increase program effectiveness. For many years, “e-Government” has been a major contributor to meeting these challenges. In recent years Russia has made good progress on its existing e-Government strategy for providing digital services in parallel with other channels. To assist the Government of the Russian Federation with its plans to develop and launch a project that will be designed to address these issues and move the country towards a Digital Government, this report from the World Bank team sets out high level recommendations that are tailored to the needs of Russia, and that are in line with the best international practices. The analysis shows that the situation with the monitoring of e-Government development in the Russian Federation as a whole is not bad. There are large amounts of data on various aspects of using ICT for public administration and local self-government. Most of measurable indicators used in Russia, as in many other countries, relate to assessments of the level of e-Readiness of the country, and of particular regions or industries. To conclude, for Russia, as well as for other countries, there is a challenge to create a new system of monitoring for the use of ICT for public administration in the context of proper Digital Government maturity models.